The role of second-hand markets in circular business: a simple model for leasing versus selling consumer products. Issue 1 (17th January 2018) - van Loon, Patricia; Delagarde, Charles; Van Wassenhove, Luk N.
Abstract : This paper explores the role of the second-hand market when transitioning to a closed-loop system where products are leased multiple times. The total cost of ownership for consumers and profitability for manufacturers are compared in circular and linear business cases. We find that while second-hand markets were beneficial for manufacturers of durable goods in a linear system, since they increased the consumers' willingness-to-pay for new products, the same second-hand markets might restrict the profitability of a closed-loop business model. A high resale value results in a relatively low cost of ownership in the sales system and additional activities in the closed-loop model (such as managing the lease contracts and refurbishment) add significant costs to the supply chain. Consequently, the economic (and environmental) benefits of leasing products already traded on second-hand markets in the linear system are often limited. Our simple analytical model allows a quick and dirty analysis of multiple scenarios with a minimum of inputs. We argue that manufacturers lack these kinds of models to guide them in navigating circular economy business models.